Independensi Media Massa di Indonesia pada Tahun Politik 2024: Studi Kasus pada Kompas.com - Suprayitno, Dede; Alfisyahri MJ, Khairun (IKOMIK: Jurnal Ilmu Komunikasi dan Informasi, 2025)
Indonesia faces general elections in 2024. At this time, the media has an important role in publishing news to the public, including in creating issues for the public. This research uses a case study method on Kompas.com with a qualitative approach. This research uses the Agenda Setting theory developed by Maxwell McCombs and Donald Shaw, to find out how the media creates the issues that are reported. Data collection was carried out through observation, in-depth interviews and document study. The results of research deepened through an inductive perspective show that Kompas.com shows independent reporting. This attitude is built from the editors' frame of mind from within the editorial room. There is freedom offered by the editorial team to journalists in covering political issues. Regarding the selection of political news issues, the editorial team also takes a balanced attitude in presenting the news. The editors also appear to be careful in selecting sources, because they can determine the direction of news that tends to be political. The use of data in the journalistic process helps Kompas.com to present higher quality news.